Getting the Message Across / A Guide to Directing Corporate Communications - Churchill David; Jennings Marie (Director Books, 1988)
Acknowledgements, Introduction, Corporate Communications and the Company, The Corporate Dialogue, Grasping the Market Research Nettle, Choosing and Using a Consultancy, Media Relations, Communicating the Company's Record of Achievement, Key Relationships, Managing the Communication Function, Value for Money in Corporate Communications, The End Result - Consumer Affairs.
Acknowledgements, Introduction, Corporate Communications and the Company, The Corporate Dialogue, Grasping the Market Research Nettle, Choosing and Using a Consultancy, Media Relations, Communicating the Company's Record of Achievement, Key Relationships, Managing the Communication Function, Value for Money in Corporate Communications, The End Result - Consumer Affairs.